Memanaj Ragam Format Acara Dakwah - Erwan Effendi; Hadi Syahputra; M. Ariiq Hawwari; Siti Wahyummi Nur Jannah (Dakwatussifa: Journal of Da'wah and Communication, 2023)
Management is the ability to organize and lead in such a way that everything goes according to the vision to be achieved. With the management of da'wah events/programs, da'wah activities can be well structured. Managing various da'wah programs/events as a process of compiling forms and structures in various religious events from beginning to end with the aim of inviting mad'u to do good and forbidding evil. The various forms of well-managed da'wah events make da'wah offerings very interesting, creative and innovative. Kata Kunci : da’wah event, manajement